Exploring extensive reading implementation in higher education: A TPACK-based analysis - Harimurti, Keke Febrian; Wulyani, Anik Nunuk; Setyowati, Lestari (Universitas Islam Negeri Palangka Raya, Indonesia, 2025)
Considering multiple analyses on the effectiveness of extensive reading (ER) in higher education, this study addresses the lack of empirical evidence regarding the implementation of ER in higher education, particularly in an Indonesian university. This study explored the importance of understanding how the integration of technological pedagogical and content knowledge (TPACK) in ER practices in a higher education context. Through a qualitative case study involving one lecturer from a state university in East Java, Indonesia, the data were obtained through interviews and classroom observations to facilitate triangulation and ensure its credibility, and then analyzed using thematic analysis. The findings demonstrated that ER was carried out at the university, aligning with the ER principles set forth by Day and Bamford (2002) and Hedgcock and Ferris (2009). Moreover, from the TPACK framework, technology mainly served as a resource, management system, and content delivery tool, facilitating smoother ER practices. The strategic combination of materials and teaching methods also supported ER activities, enabling students to follow instructions and meet course objectives efficiently. Thus, this research offered valuable insights for universities to implement ER courses, providing evidence-based practices for lecturers to optimize teaching methods, tools, and resources on ER practices in higher education settings.